Factors in illicit bioweapons programs: case studies of the Soviet Union/Russia and Iraq - Smithson, Amy E. (Frontiers in Political Science, 2025)
Germ weapons can devastate human, animal, and plant populations, and the universe of possible biowarfare agents is expanding with advances such as CRISPR and AI. Political leaders order the development and use of weapons, and they also pass laws and establish regulations and policies to govern their societies. Such political factors can frame the choice of biological agents; the characteristics of research, development, testing, and production programs; and military doctrine for biological warfare. These other factors can be identified, evaluated, and used to inform efforts to detect proliferation. Therefore, this article presents case studies elaborating the sociological context, motivations, organizational structure, level of science, technology, and safety, military doctrine, and visibility of the Soviet/Russian and Iraqi bioweapons programs. The article also contrasts the case studies and draws insights from each.